2017
DOI: 10.1111/jfd.12707
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility, behaviour, and retention of the parasitic salmon louse (Lepeophtheirus salmonis) differ with Atlantic salmon population origin

Abstract: Atlantic salmon populations across the world have diverse ecological and evolutionary histories, from wild anadromous or landlocked, to domestication and genetic modification. The natural host behaviours confer protection from infestation by ectoparasitic salmon lice Lepeophtheirus salmonis, yet whether genetic origin results in different behaviours and thus susceptibility to infestation is unknown. In common garden experiments, we tested antiparasite behaviours, susceptibility and retention of salmon lice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…Further, Caligus infection is known to induce increased enzyme activity in muscle tissue ( Vargas-Chacoff et al, 2017 ), and behavioral changes in the fish such as flashing and jumping are associated with ectoparasite removal ( Furevik et al, 1993 ; Magnhagen et al, 2008 ). It has been recently reported that inactivity or reduced swimming activity contribute to resistance to sea lice ( Bui, 2017 ), so it is possible that the high lice counts of susceptible fish in this study are due to higher activity levels with associated expression of muscle contraction related genes. In turn, high lice burden can provoke behavioral responses increasing fish activity, which results in the up-regulation of muscle genes, increasing the expression differences between resistant-passive-low lice fish and susceptible-active-high lice fish.…”
Section: Resultsmentioning
confidence: 89%
“…Further, Caligus infection is known to induce increased enzyme activity in muscle tissue ( Vargas-Chacoff et al, 2017 ), and behavioral changes in the fish such as flashing and jumping are associated with ectoparasite removal ( Furevik et al, 1993 ; Magnhagen et al, 2008 ). It has been recently reported that inactivity or reduced swimming activity contribute to resistance to sea lice ( Bui, 2017 ), so it is possible that the high lice counts of susceptible fish in this study are due to higher activity levels with associated expression of muscle contraction related genes. In turn, high lice burden can provoke behavioral responses increasing fish activity, which results in the up-regulation of muscle genes, increasing the expression differences between resistant-passive-low lice fish and susceptible-active-high lice fish.…”
Section: Resultsmentioning
confidence: 89%
“…In communal and single fish tanks, between 36% and 51% of mobile lice can be lost over 24 days (Hamre & Nilsen, 2011). Interestingly, farmed strains of salmon lost 27%–32% of attached lice over 34 days in tanks; however, this was not the case with wild and landlocked Atlantic salmon in the same tanks (Bui, Dalvin, et al, 2018), suggesting a genetic effect on lice developmental success or movement between hosts. However, experience in unspecific loss of lice over development and between replicate tanks has been reported as quite high and very variable (Bjørn & Finstad, 1998; Hamre, Glover, & Nilsen, 2009), but when infested fish are housed in an very controlled manner, variation and loss of lice can be almost eliminated (S. Dalvin, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Bui et al. (2018)). Retention of lice is highly dependent on the size and density of host fish and tank environment (Hamre et al., 2009) and therefore varies between experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkably low louse loss observed contrasts other reports. Whereas several experiments have observed little loss of lice in fish from infection to development of preadults (Bui et al., 2018; Fast et al., 2002; Grimnes & Jakobsen, 1996), considerable loss was reported during the preadult to early adult phase (Bjørn & Finstad, 1998; Bui et al., 2016; Dawson, Pike, Houlihan, & McVicar, 1997; Hamre et al., 2009; Hamre & Nilsen, 2011). Loss is likely to be a result of a number of processes including behaviour and response of the fish, accidental detachment of parasites from the fish through contact with tank surfaces, and movement of the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation